Cisco BGP-4 command and configuration handbook - Parkhurst, William R. (CCIE professional development., 2001)
"Cisco BGP-4 Command and Configuration Handbook is a clear, concise, and complete source of documentation for all Cisco IOS Software BGP-4 commands. If you are preparing for the CCIE written and lab exams, this book can be used as a laboratory guide to learn the purpose and proper use of every BGP command. If you are a network designer, this book can be used as a ready reference for any BGP command." "Cisco BGP-4 Command and Configuration Handbook provides example scenarios that demonstrate the proper use of every BGP-4 command, which can be implemented using a minimum number of routers. This will enable you to learn each command without requiring an extensive and expensive lab configuration. The scenarios are presented so that the purpose and use of each command can be demonstrated without clouding the issue. Some of the examples lead you into common non-working situations in order to reinforce the understanding of the operation of the particular BGP command."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved